Pemberdayaan Masyarakat Melalui Inovasi Puding Bunga Telang (Clitoria Ternatea) Sebagai Upaya Pengendalian Hipertensi Di Rw 03 Kelurahan Wonorejo - Indri Eka Wahyuni; Rizka Fikrotul Azizah; Abdul Hamid; Novi Mamluatul Ilmiyah; Afrah Amani; Chila Liyah Nur Sabrina; Robert Aditya Wijanarko; Putri Dini Andika; Revy Marisca Eka Febriyanti; Riska Aprilia; Muhammad Farhan Maulana; Gadis Nur Fitri; Millah Kamilah Shouniyah; Nanda Exchi Alfiyadi; Ferdinan Farhan Syafi; Dwi Nirmala Sari; Nisfi Azizah Fitriyani; Mamen Sanz; Priyo Mukti Pribadi Winoto (CV. SINAR HOWUHOWU, 2026)
Hypertension is a non-communicable disease with a high prevalence in Indonesia and is a major health problem in RW 03, Wonorejo Village, Tegalsari Subdistrict, Surabaya. This area has the potential of butterfly pea flower (Clitoria ternatea), which contains flavonoids and antioxidants that may help lower blood pressure. This community service activity aims to empower the community through an innovation in processing butterfly pea flowers into pudding as an educational medium for hypertension control. The activity was carried out through stages of initial observation, coordination with partners, program planning, implementation, evaluation, and follow-up, targeting the community of RW 03. The results show that the butterfly pea flower pudding product served as an engaging and easily accepted health education medium, although the activity did not include a demonstration or hands-on processing session with participants, so the community's direct experience remained limited. This activity is expected to encourage the community to make sustainable use of local resources as part of promotive and preventive efforts in hypertension control.